Solvent extraction and identification of active anticariogenic metabolites in Piper cubeba L. through ¹H NMR-based metabolomics - Raja Mazlan, Raja Nur Asila (2018)
Dental caries is a noticeable infection in human. Even though rarely a life threatening, dental caries is still a major hassle for health provider companies. Piper cubeba L. with potential in elimination of dental caries has been studied. The aim of this study was to determine the effects of using different solvents for extraction, liquid-liquid partition, concentrations of extracts and fractions on the anticariogenic activity against Streptococcus mutans KCCM3309, S. sobrinus ATCC33478 and Actinomyces viscosus ATCC15987. The potentially active anticariogenic metabolites were identified by mean of proton nuclear magnetic resonance (1H NMR) via multivariate data analysis (MVDA). The disc diffusion assay results of extracts and fractions showed the range of inhibition zone between 7.00 to 12.67 mm. Minimum inhibitory concentrations (MIC) data showed P. cubeba L. extracts and fractions at concentrations ranged from 0.10 mg/mL to 3.15 mg/mL have inhibited 99% bacterial growth. The ability of the extracts or fractions to kill at least 99% of bacteria was shown by minimum bactericidal concentrations (MBC) data, wherein the range for extracts and fractions spread from 0.10 mg/mL to 25.0 mg/mL. Bactericidal endpoint was determined to be in the range of 0.20 mg/mL to 3.80 mg/mL through time-kill curve assay of P. cubeba L. extracts at concentration of 0× MIC, 1/2× MIC, 1× MIC, 2× MIC and 4× MIC. The results revealed that all tested bacteria were susceptible to P. cubeba L. extracts and fractions. Varying solvents used for extraction, liquid-liquid partition and concentrations of extracts and fractions have influenced the antibacterial activity. For MTT cell proliferation assay, the percentage of RAW 264.7 cell viability approximately 80% and above are considered as not toxic. From the assay, methanol extract, ethanol extract, hexane fraction and ethyl acetate fraction were not toxic at the concentration of ≤ 62.5 μg/mL, while hexane extract and aqueous methanol fraction were at ≤ 125 μg/mL. Anti-inflammatory properties of the extracts and fractions were evaluated by nitric oxide (NO) production in stimulated RAW 264.7 cells by lipopolysaccharide (LPS). The lowest NO production observed in methanol extract was at concentration 62.5 μg/mL with 22.98 μg/mL NO production, suggesting that methanol extract might be a suitable candidate for the anti-inflammatory agent. Twelve metabolites have been identified based on the 1H NMR, which were cubebin (1), yatein (2), hinokinin (3), dihydrocubebin (4), dihydroclusin (5), cubebinin (6), magnosalin (7), p-cymene (8), piperidine (9), cubebol (10), D-germacrene (11) and ledol (12). The metabolites that contributed to separation in principal component analysis (PCA) between hexane and other extracts were detected as cubebol, ledol, Dgermacrene and piperidine. Meanwhile cubebol, ledol, D-germacrene and p-cymene caused separation of hexane fraction from ethyl acetate and aqueous methanol fractions. The partial least squares (PLS) model showed that higher biological activity was related more towards the polar solvents. Despite, the active metabolites also present in the non-polar solvents. The metabolites that related to the MBC were identified as cubebol, D-germacrene and ledol. p-cymene, cubebol and ledol were observed to contribute to the activity for anti-inflammatory in stimulated RAW 264.7 cells by LPS. In summary, P. cubeba L. extracts and fractions exhibited antibacterial and anti-inflammatory activity and have potential to be developed as anticariogenic agent.